Detection Accounting Fraud: Role Internal Auditor and Whistleblowing Data System in Study Literature - Prasetiyo, Yudhi; Riyani, Etik Ipda; Novita Nugraheni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted with the aim of finding out and analyzing the role and influence of the independence of internal auditors and whistleblowing data systems in detecting accounting fraud in private, public sector organizations or non-governmental organizations. This research is qualitative research with descriptive analysis methods based on literature studies with secondary data through scientific articles, news, books, previous research and the internet over the last five years, namely 2019-2023. The results of this research are that the independent attitude of internal auditors and the whistleblowing data system is very good and has a significant effect on detecting accounting fraud. Although there are several factors that influence the effectiveness of implementing an independence attitude and whistleblowing system, such as the control environment, relationships with clients, incentives for whistleblowers, and binding regulations and other related factors.